2020
DOI: 10.1088/2053-1591/ab6e30
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between thermophysical properties and structure of CMAS glass melts based on chromium slag

Abstract: In an attempt to determine the relationship among the network structure, viscosity, electrical conductivity, surface tension, and density of chromium-containing glass melts, the variation in glass melt thermophysical properties of the CaO-MgO-Al 2 O 3 -SiO 2 quaternary system were investigated by comprehensive physical property analysis and Raman spectroscopy. The results demonstrated that the network structural units Q n (n=0, 1, 2, 3) coexisted in the glass melts and their mutual transformation caused chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Chengjun LIU, 1,2) Rui ZHANG, 1,2) Yifan MENG, 1,2) Zhen WANG, 1,2) Shiyan JIAO, 1,2) Jixiang JIA 3) and Yi MIN 1,2,3) * the attraction force between positive and negative ions and increase surface tension. Sukenaga et al 8) showed that the variation of oxygen atom environment is the main reason for the difference in the surface tension of the CaO-SiO 2 , CaO-SiO 2 -Al 2 O 3 and CaO-SiO 2 -Al 2 O 3 -MgO slags.…”
Section: Mirco-level Insight Into the Surface Tension-structure Relationship Of Molten Cao-mgo-sio 2 -Fe X O-p 2 O 5 Slagsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chengjun LIU, 1,2) Rui ZHANG, 1,2) Yifan MENG, 1,2) Zhen WANG, 1,2) Shiyan JIAO, 1,2) Jixiang JIA 3) and Yi MIN 1,2,3) * the attraction force between positive and negative ions and increase surface tension. Sukenaga et al 8) showed that the variation of oxygen atom environment is the main reason for the difference in the surface tension of the CaO-SiO 2 , CaO-SiO 2 -Al 2 O 3 and CaO-SiO 2 -Al 2 O 3 -MgO slags.…”
Section: Mirco-level Insight Into the Surface Tension-structure Relationship Of Molten Cao-mgo-sio 2 -Fe X O-p 2 O 5 Slagsmentioning
confidence: 99%
“…To control metallurgical behavior in smelting process, numerous studies on the surface tension of slag have been carried out. [3][4][5][6] Yuan et al 7) considered that cation potential (z/r) is closely related to surface tension, and a larger value of z/r in the SiO 2 -FeO-MgO-CaO system could enhance…”
Section: Introducitonmentioning
confidence: 99%